STRATEGI PENGEMBANGAN USAHA UNTUK MENGATASI PERSAINGAN ( STUDI KASUS PT. KIMIA FARMA JAKARTA ) - Marlina Rahmi Shinta Permatasari (Universitas Bina Sarana Informatika, 2017)
ABSTRACTDevelopment of business strategy is an important thing that can determine the success of businessThis strategy is on interesting thing to discuss. It is shared in business development. If a company does something wrong in determining the strategy, it will make many problems.To determine development of business strategy, it has to be agreed with di situation of the business, because both of them will influence each other.The strategy can be directed to the useful resources that are used to the company progress. With the result of the progress the company can reach its aim and target.Keywords : Business strategy, Business development, Targets